The relationship between locus of control and pre-competitive anxiety in highly trained soccer players - Amar, Imen Ben; Gomni, Chiraz; Chortane, Oussama Gaied; Khmiri, Aymen; Ghouaiel, Rania; Baker, Julien S. (Frontiers in Psychology, 2023)
Previous studies have not considered the potential association between locus of control and precompetitive anxiety in elite soccer players. Accordingly, this cross-sectional study examinedThe prediction of locus of control on precompetitive anxiety in highly trained cadet soccer players. Based on a literature review, our research question was: can the locus of control be considered as an explanatory element of precompetitive anxiety?. Thirty-five Tunisian highly trained soccer players licensed from two regional soccer clubs aged between 15 and 16 years participated in the resent study. All participants were evaluated using the Competitive State Anxiety Inventory-2 (CSAI-2) and the Internal-External Locus of Control Scale. The relationship between measures of anxiety, self-confidence and the locus of control scores were analyzed using Pearson's product-moment correlation coefficient. Further, multiple linear stepwise multiple regression models were calculated to determine the most robust predictors of the locus of control. Based on our findings, the regression analysis explains up to 21.3% of the total variation of our independent variable (locus of control) and explains only 21.3% of the variability of our dependent variable somatic anxiety. Furthermore, locus of control explains 61.9% of the variability in self-confidence. The locus of control can be used for the detection and selection of young athletic talent to identify individuals with the best psychological aptitude to cope with psychological problems related to sports performance. Preparing highly trained soccer players on how to deal with their anxiety could prevent them from becoming overwhelmed when they feel powerless to change their situation during competition.